Small Step Frequency Changes Due to Footwear Condition Have No Effect on Running Economy - Warne, Joe; Moran, Kieran Andrew; Warrington, Giles D (Sports Medicine International Open, 2018)
The aim of this study is to examine if small increases to step frequency associated with minimal footwear can influence Running Economy (RE). Twelve club-level runners with eight weeks of minimal footwear experience were recruited (age, 41±9 years; stature, 177.2±10.4 cm; body mass, 72.6±10.2 kg; V˙O2max, 52.1±7.5 mL·min−1·kg−1). Two 6-min RE tests, one in minimal footwear and one in conventional running shoes were performed at 11 km·h−1. Two more 6-min tests were completed during which step frequency was controlled using a metronome at the cadence of the opposite footwear condition (RErevSF). Comparisons were completed between the same footwear using repeated measures ANCOVA. The increase in step frequency for minimal footwear vs. conventional running shoes was 7.3±2.3 steps per minute (3.9% difference; 95% CI of difference [5.87 to 8.80 steps/min]; p≤0.001; Cohen’s d=0.70). No significant differences were identified between RE and RErevSF for minimal footwear (40.72±4.08 vs. 41.09±4.19 mL·min−1·kg−1; 95% CI of difference [–1.71 to 0.97]; p=0.55; Cohen’s d=0.09), or conventional running shoes (42.04±4.68 vs. 41.74±5.09 mL·min−1·kg−1; 95% CI of difference [–0.78 to 1.37]; p=0.55; Cohen’s d=0.06). Small changes in step frequency (~4%) did not have any significant impact on RE.
Keywords: performance; footwear; running technique; cadence